Influence of degradation on the electrical conduction process in ZnO and SnO2-based varistors - Ponce, M. A.; Ramirez, M. A. [UNESP]; Parra, R.; Malagu, C.; Castro, M. S.; Bueno, Paulo Roberto [UNESP]; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2010)
The conduction process during degradation, promoted by the application of fixed dc bias voltage at different temperatures (thermal steady states) and current pulses 8/20 mu s on ZnO and SnO2-based varistors, was studied comparatively in the present work. The electrical properties of the varistor systems were highly damaged after degradation with current pulse 8/20 mu s. Variations on the potential barrier height and donor concentration were calculated by fitting the experimental data from impedance spectroscopy measurements assuming the formation of Schottky barriers at the grain boundaries and electrical conduction to occur due to tunneling and thermionic emission. (C) 2010 American Institute of Physics. [doi:10.1063/1.3490208]